Antibacterial Activity of Ethanol Extract of Qust Al Hindi Plant Root (Saussurea Lappa) Against Bacteria Staphylococcus aureus and Escherichia coli by TLC-Bioautography - Muthia, Farah; Sukmawati, Sukmawati; Fitriana, Fitriana (Journal Microbiology Science, 2023)
The Indian Costus plant (Saussurea lappa) possesses the ability as an antibacterial, which contains alkaloid compounds, whereas this study aims to determine the antibacterial activity of ethanol extract of Indian Costus plant root (Saussurea lappa). The extraction process of Indian Costus plant root simplicia (Saussurea lappa) was carried out using the Soxhlet method with 96% ethanol as a solvent, and then evaporated with a rotavapor to obtain a viscous extract. Screening tests were carried out by giving ethanol extract of Indian Costus plant root (Saussurea lappa) with a concentration of 0.1% to 2 test bacteria, namely Staphylococcus aureus and Escherichia coli. Thereafter, the Thin Layer Chromatography-Bioautography test was carried out, followed by identification of chemical compounds. The screening test results obtained showed that the ethanol extract of Indian Costus plant root (Saussurea lappa) provided activity against 2 test bacteria at a concentration of 0.1%. The Thin Layer Chromatography-Bioautography test results indicated that there were 3 spots that were formed with Rf values of 0.67, 0.60, 0.54, 0.45, 0.43 providing activity on Staphylococcus aureus and Escherichia coli bacteria. The chemical identification of ethanol extract of Indian Costus plant roots (Saussurea lappa) yeilded positive result for the presence of alkaloids. Based on the activity of the ethanol extract of Indian Costus plant root (Saussurea lappa), it is known that it has potential as an antibacterial.